Brain fag and burnout: a comparison of two exhaustion syndromes among adolescents in Nigeria - Emmanuel Aniekan Essien; Bassey Eyo Edet; Chidi John Okafor; Halilu Abdullahi; Owoidoho Udofia (Open Journal of Psychiatry and Allied Sciences, 2022)
Background: Brain fag and burnout are exhaustion syndromes first described in different cultural contexts, and both occur among students. They share some similarities but have not been compared in research. Objective: This study sought to determine the relationship between brain fag and burnout among adolescent students in Calabar, Nigeria. Method: In this cross-sectional study, 810 students were recruited from ten secondary schools in Calabar. The Brain Fag Syndrome Scale and the Maslach Burnout Inventory-Student Survey were administered. Results: The mean sample age was 15.93 (±1.35) years, and the gender distribution was approximately equal. The emotional exhaustion and cynicism dimensions of burnout were significantly associated with brain fag syndrome (p<0.05). Respondents with high emotional exhaustion (Odds ratio [OR]=3.3, confidence interval [CI]=2.06-5.36) and cynicism (OR=2.7, CI=1.66-4.39) were more likely to meet the threshold for brain fag syndrome. Principal components analysis of items from both instruments yielded a four-factor structure, and one had substantial loadings from both scales. Conclusions: Both syndromes are related, probably due to an overlap in core exhaustion symptoms. More research is needed to elucidate their relationship further.